Biofunctionalization of Porous Titanium Oxide through Amino Acid Coupling for Biomaterial Design - Canepa, Paolo; Gregurec, Danijela; Liessi, Nara; Rotondi, Silvia Maria Cristina; Moya, Sergio Enrique; Millo, Enrico; Canepa, Maurizio; Cavalleri, Ornella (Materials, 2023)
Porous transition metal oxides are widely studied as biocompatible materials for the development of prosthetic implants. Resurfacing the oxide to improve the antibacterial properties of the material is still an open issue, as infections remain a major cause of implant failure. We investigated the functionalization of porous titanium oxide obtained by anodic oxidation with amino acids (Leucine) as a first step to couple antimicrobial peptides to the oxide surface. We adopted a two-step molecular deposition process as follows: self-assembly of aminophosphonates to titanium oxide followed by covalent coupling of Fmoc-Leucine to aminophosphonates. Molecular deposition was investigated step-by-step by Atomic Force Microscopy (AFM) and X-ray Photoemission Spectroscopy (XPS). Since the inherent high roughness of porous titanium hampers the analysis of molecular orientation on the surface, we resorted to parallel experiments on flat titanium oxide thin films. AFM nanoshaving experiments on aminophosphonates deposited on flat TiO2 indicate the formation of an aminophosphonate monolayer while angle-resolved XPS analysis gives evidence of the formation of an oriented monolayer exposing the amine groups. The availability of the amine groups at the outer interface of the monolayer was confirmed on both flat and porous substrates by the following successful coupling with Fmoc-Leucine, as indicated by high-resolution XPS analysis.
CRIS-Team Scopus Importer:2023-02-03
Keywords: AFM; amino acid coupling; aminophosphonates; Fmoc-Leucine; nanoshaving; porous titanium oxide; XPS